Patterns and drivers of health care use in long-term childhood cancer survivors: A systematic review. (December 2017) - van Breeschoten, J.; De Abreu Lourenco, R.; Signorelli, C.; Haas, M.; Cohn, R.J.; Wakefield, C.E.; Fardell, J.E.
Highlights: Twenty-two studies presenting data on 88, 787 experiences of health care use from childhood cancer survivors were included in the systematic review. An average of 64.5% of childhood cancer survivors engaged with some form of health care utilisation in the time frames studied. An average of 56.3% of childhood cancer survivors used health screening services (e.g. cancer, cardiac and bone health). Older age, higher income, private health insurance, chronic health conditions, prior radiotherapy, attending follow-up care and being female were associated with increased health care utilisation. Abstract: Background: Childhood cancer survival is increasing. But cancer and treatment late-effects can lead to ongoing health care use. We summarised the literature on the patterns and drivers of health care use among childhood cancer survivors. Method: Pubmed, Embase and Medline were searched for studies reporting health care use in childhood cancer survivors. Results: We included 22 studies, covering 88787 experiences of health care use. The proportion of survivors using follow-up care, physician visits, specialist visits, hospitalisations, dental care and screening services varied (36.4%–88.8%). Participation in screening was below recommendations (11.5%–81%). Drivers of increased health care use included higher income, private health insurance, attending follow-up care, chronic health conditions, prior radiotherapy, being female and older age. Conclusion: Sociodemographic and clinical factors result in differences in health care use. Future research could investigate whether such use is appropriate and how survivors might be engaged to receive care appropriate to manage their needs.